The Alteration Profiles of m6A-Tagged circRNAs in the Peri-Infarct Cortex After Cerebral Ischemia in Mice - Li, Yudi; Li, Hanzhao; Luo, Yang; Li, Xiaoqiang; Chen, Zhefeng; Zhang, Wanzhou; Li, Fangming; Ling, Li (Frontiers in Neuroscience, 2022)
Abstract: The N6-methyladenosine (m6A) modification acts as a dynamic regulatory factor in diseases by regulating the metabolism and function of the transcriptome, especially mRNAs. However, little is known regarding the functional effects of m6A modifications on circRNAs. In this research, we established a distal middle cerebral artery occlusion (MCAO) model in adult C57BL/6J mice. The mice were divided into three groups: sham surgery, 3 days after MCAO (3d), and 7 days after MCAO (7d). Real-time quantitative polymerase chain reaction (RT-qPCR) demonstrated that the mRNA expression levels of m6A-related methyltransferases (METTL3, METTL14), demethylases (FTO, ALBKH5), and reading proteins (YDFTH1, YDFTH3) were altered compared to the sham group. Furthermore, the translation level of ALBKH5 and YTHDF3 was significantly decreased in the 3d group while increased in 7d group. Methylated RNA immunoprecipitation (MeRIP) and circRNA microarray indicated 85 hypermethylated and 1621 hypomethylated circRNAs in the 3d group. In the 7d group, the methylation level increased in 57 and decreased in 66 circRNAs. Subsequently, our results were verified by MeRIP and RT-qPCR. Bioinformatics analysis was performed to analyze the functions of differentially m6A-modified circRNAs. We found some m⁶A modified circRNAs associated with cerebral infarction, providing a new direction for the molecular mechanism of stroke.